Authentic Performance as a Challenge to the State - Ronis, Eric (InTensions, 2010)
Authenticity is a key source of power for social and political protest groups who engage in radical street performance. Publicly performed authenticity circumvents the power of the State (and institutions that are extensions of the State) in its control of public discourse. Such performance serves to create an immediate relationship between protesting groups and the more mainstream public by reducing or collapsing the domain of “critical” distance. This paper examines two specific case studies, Las Madres and Otpor, and analyses the form of street theatre in which they engaged. The connection between a group’s ethos and their logos emerges as an essential element for the success of group protest.